Factors affecting the ability to speak in children with autism spectrum disorders - Siti Maemonah; Hamidah Hamidah; Hari Basuki Notobroto; Dony Sulystiono; Luluk Widarti (Journal of Public Health Research, 2021)
Background: Communication deficit is one of the characteristics of autism spectrum disorder. Some children with this condition cannot communicate verbally and some have very limited speech skills. This study aims to analyze the factors that affect speaking ability in children with autism, namely age, sex, emotions, attention, and memory. Design and Methods: This study used a correlational analytical design with a retrospective cohort design. Data were obtained using questionnaires and scales. Furthermore, emotional factors, attention, memory, and age were analyzed for their effects on speaking ability using the Pearson test, while sex was analyzed for their effects on speaking ability using the Eta test. Results: The results showed that there was a significant effect of attention and age on the speaking ability of children with autism spectrum disorders. Furthermore, it showed that there was a significant effect of emotion on attention. Conclusions: It was concluded that attention and age affect the speaking ability of children with autism spectrum disorder. Meanwhile, attention in affecting speaking ability is influenced by emotions. Therefore, to improve speaking ability, good emotional management and increased attention is required.